Green rush and red warnings: Retrospective chart review of adverse events of interactions between cannabinoids and psychotropic drugs - Chrobak, Adrian Andrzej; Woroń, Jarosław; Siwek, Marcin (Frontiers in Pharmacology, 2024)
Aim: Our objective was to systematically assess the prevalence and clinical features of adverse events related to interactions between cannabinoids and psychotropic drugs through a retrospective chart review.Methodology: 1586 adverse event reports were assessed. Cases included in the analysis showed a high probability of a causal relationships between cannabinoid-psychotropic drug interactions and adverse events. Data extracted included age, sex, psychotropic drug, cannabinoid products, other medications, and the clinical outcomes and mechanisms of these interactions.Results: Cannabinoids were involved in 8% of adverse events associated with the concomitant use of psychotropic drugs and other preparations. We identified 20 reports in which side effects presented a causal relationship with the use of psychotropic drugs and cannabinoids. Preparations containing 18% or more tetrahydrocannabinol (THC), presented significant side effects with the following antidepressants: mianserine (restless legs syndrome, urogenital pain, ventricular tachycardia), mirtazapine (pancreatitis, hyperhidrosis, arthralgia), quetiapine (myocarditis, renal failure, bradycardia, sialorrhea), haloperidol (ventricular arrhythmia, prolonged QTc), aripiprazole (prolonged QTc), ventricular tachycardia) and cariprazine (stomach pain, hepatotoxicity), sertraline (ataxia, hyperactivity, coma, hallucinations, anxiety, agitation, tachycardia, panic attacks, disorientation, headache, dizziness, blurry vision, severe emesis, xerostomia, dry eyes), trazodone (disorientation, memory impairment, sedation), fluvoxamine (tachycardia, tachypnoea, dysarthria, auditory hallucinations). Two out of 20 reports (10%) analyzed in our study was related with the simultaneous use of cannabidiol (CBD) oil and sertraline. Concomitant use of those substances was associated with the adverse events in form of diarrhea, emesis, fever and severe fatigue.Clinicians need to closely monitor adverse events resulting from the combined use of cannabinoids and psychotropic medications. The accumulation of side effects and pharmacokinetic interactions (including CYP and p-glycoprotein inhibition) between these drugs can lead to clinically significant adverse outcomes.